Ablated precursor plasma and evolution of magnetic field of exploding cylindrical thin liner. (4th February 2021) - Zhang, Daoyuan; Wu, Jian; Chen, Ziwen; Lu, Yihan; Shi, Huantong; Li, Xingwen; Jia, Shenli; Wang, Guanqiong; Gan, YunDan; Zhang, Jiangbo
Abstract: The formation of precursor plasma and ablation dynamics of Al thin liner explosion are investigated in this manuscript. The size of 12 mm in diameter, 10 μ m in thickness Al liners are exploded on the Qin-1 facility (about 450 ns, 450 kA). An axial laser shadowgraphy and interferometry platform is set up to observe the plasma dynamics inside the liner. To solve the problem that the inside plasma density of the liner cannot be absolutely calibrated due to the lack of a zero plasma density area, we have established a CW laser interference system using a streak camera which can trace the interference lines over time. Low-density (10 −7 −10 −6 g cm −3 ) precursor plasma is generated from the interior wall and flows towards the center with a velocity of about 150–200 km s −1, thus forming a column with high electron density by accumulation. Simultaneously, a high-density plasma layer flows toward the center at about 10 km s −1 . The electron density of the central plasma column rises up rapidly after the precursor reaches the center and achieves 2.5 × 10 18 cm −3 at 280 ns after the current starts. To fully understand the process, we have used the resistive magnetohydrodynamic code FLASH to realize a simulation to study interior precursor dynamics. We compared these simulation results with our experiments. Finally, we measured the voltage for the whole process and derived the inductance change and effective current radius. We compared the simulated current density distribution with the experimental result which proves that a considerable amount of current flows through the center plasma column, making the effective radius of current become smaller over time.